MANHAJ DZAWIN AL-NAZHAR: WARISAN INTELEKTUAL AT-TARMASI (W 1920 M) BAGI PENDIDIKAN HADIS DI NUSANTARA - Doni Saputra (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
Hadith education in the archipelago was initially not given much attention by some seekers of knowledge due to the lack of references offered at that time. However, at-Tarmasi (d. 1920 AD) emerged as a differentiator by introducing the book Manhaj Dzawin Al-Nazhar as the main reference in studying hadith and the sciences within it. This article serves as a resource to explore the role of at-Tarmasi (d. 1920 AD) in the advancement of hadith education in the archipelago through his book Manhaj Dzawin Al-Nazhar. Using a historical approach as a step to seek in-depth information. The steps taken by the author involve four stages: heuristic, criticism, understanding, and destruction, which result in the conclusion that the book Manhaj Dzawin Al-Nazhar is a book of ulumul hadis that serves as a reference for scholars in the archipelago to study hadith. This book also provides seekers of knowledge with an understanding of the importance of a system for studying hadith, which has been adopted by many scholars from the archipelago to teach hadith education in the region